Spatial effects of environmental regulation on high-quality economic development: From the perspective of industrial upgrading - Li, Yangyang; Liu, Weijiang (Frontiers in Public Health, 2023)
Studying the spatiotemporal heterogeneity of environmental regulations on high-quality regional economic development is of enormous practical value in the context of sustainable economic, social, and environmental development. Few studies, however, examine the regional heterogeneity path of environmental regulation affecting economic development from the standpoint of upgrading industrial structure. This research investigated the spatial distribution traits of high-quality regional development based on the construction of a comprehensive assessment index system for the high-quality economic development. The economic geography nested spatial Durbin model is then used to perform an empirical test. The findings demonstrate that: (1) The high-quality economic development has obvious spatial heterogeneity, with strong local spatial agglomeration between regions; (2) Environmental regulation and the modernization of the industrial structure are significant variables influencing the high-quality economic development, but their development is not balanced; (3) Environmental policies promote high-quality regional development through distinct channel. Formal environmental regulation promotes economic development through rationalizing industrial structure, while informal environmental regulation does so through industrial structure upgrading. Further, the above both have positive spatial spillover effects on adjacent areas. Therefore, the regional heterogeneity of environmental regulation and industrial structure are of great significance in promoting the high-quality and sustainable development of regional economies.